Public Sector Transformation in Sustainability Era: Green Economy Policies and Community Welfare - Siti Munawaroh; Sayugo Adi Purwanto; Dwibin Kannapadang (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
In Indonesia, despite the national development agenda prioritizing the green economy, its implementation still faces challenges in coordination, bureaucratic capacity, and resistance from traditional sectors. This research aims to analyze the forms of public sector transformation within the context of green economy policies and evaluate their impact on community welfare using a mixed methods approach with an explanatory sequential design and multiple case studies. This research focuses on Surabaya City, Sigi Regency, and Balikpapan City. Primary data was collected through in-depth interviews, Focus Group Discussions (FGDs), and observations, while secondary data was obtained from policy documents and regional statistics. Data analysis was conducted thematically and comparatively, integrating quantitative and qualitative findings. The research results indicate that public sector transformation is occurring gradually, characterized by institutional strengthening, regulatory reform, and the development of participatory governance mechanisms. Surabaya City stands out in community-based waste management, Sigi Regency in forest rehabilitation and renewable energy, and Balikpapan City in green budgeting. The impact of green economy policies on community welfare proved positive, creating new jobs and increasing income in the green sector, as well as improving local environmental quality. However, this impact is not yet evenly distributed and is more pronounced at the directly involved community level.